Plasma mirror implementation on LFEX laser for ion and fast electron fast ignition. (18th September 2017) - Morace, A.; Kojima, S.; Arikawa, Y.; Fujioka, S.; Yogo, A.; Tosaki, S.; Sakata, S.; Abe, Y.; Lee, S.H.; Matsuo, K.; Sagisaka, A.; Kondo, K.; et al.
Abstract: In this work we report the successful implementation of plasma mirror (PM) technology on an LFEX laser facility at the Institute of Laser Engineering, Osaka University. The LFEX laser pulse was successfully refocused at the target chamber center (TCC) by means of a spherical plasma mirror, resulting in 5 × 10 18 W cm −2 laser intensity, with 45% reflectivity at a laser flux of about 90 J cm −2 on the PM. Experimental results show stable focusing and pointing of the LFEX pulse after PM refocusing. The contrast improvement was demonstrated by both cooler fast electron slope temperature distribution as well as by the ability to shoot sub- µ m plastic foils obtaining proton beams with maximum energy exceeding 20 MeV. Experimental results are qualitatively reproduced by 2D particle in cell simulations.